The 3-2-3 Detective Agency in The disappearance of Dave Warthog - Robinson, Fiona, 1965- (Abrams Books for Young Readers, 2009)
Five animal friends decide to form a detective agency in Whiska CIty, where they investigate the rash of disappearances linked to a poodle beauty salon.